Enhancing Sociology Students’ Research Instrument Development Skills through Digital Platform-Based Training at Halu Oleo University - Dian Puspita Rizki; Ghery Safitra Fahrun; Nada Kusuma; Muhamat Arif Afandi; Nur Azisyah Mukmin (Room of Civil Society Development, 2026)
Students often experience difficulties in developing research instruments, particularly in formulating variables, constructing indicators, designing questionnaire items, and aligning instruments with research problems. This community service program aimed to improve students’ competence in developing research instruments through structured online platform-based training. The program was conducted from November to December 2025 at the Department of Sociology, Faculty of Social and Political Sciences, Halu Oleo University, involving 94 students. The activity was implemented through preliminary needs assessment, preparation of training materials, presentations, demonstrations, guided practice, group discussions, feedback sessions, and evaluation. Students were introduced to the principles of research instrument development, including variable formulation, indicator construction, questionnaire design, validity and reliability concepts, and the use of digital platforms such as Google Forms and Microsoft Forms. The results showed notable improvement in students’ competencies. Students’ basic understanding of research instrument development increased from 38 students (40.4%) before the training to 80 students (85.1%) after the training. Their understanding of fundamental methodological principles improved from 42 students (44.7%) to 75 students (79.8%), while their ability to align research instruments with research problem formulation increased from 33 students (35.1%) to 71 students (75.5%). These findings indicate that online platform-based training contributed positively to strengthening students’ methodological competence and digital literacy in developing research instruments.